Next generation golf course: Lakeside Hills synthetic turf study - Kroen, Kevin (Kansas State University, 2009)
Synthetic turf has been used extensively for football, soccer, and baseball playing surfaces as a substitute for natural turf because of its increased durability, low maintenance costs, and similar characteristics. The popularity, however, has not extended to golf courses, a seemingly appropriate application. Golf courses are prized for their aesthetic beauty, and their maintenance requires regular, detailed upkeep with particular attention to fairways, tees, greens, hazards, and the surrounding landscape. The combination of regular mowing, watering, grooming, and application of chemicals aim to strengthen the overall appearance of the golf course, but have negative effects on the ecologic and economic values of the golf course. Is it possible to use synthetic turf to reduce the ecologic and economic effects of golf course maintenance, while still providing an aesthetically pleasing playing surface and environment? This study develops three methodologies from the primary areas of concern: ecologic, economic, and aesthetic. The ecologic method uses criteria derived from the Sustainable Sites Initiative. Criteria in the economic method assist in understanding the cost efficiency of synthetic turf over time. Finally, the aesthetic method contains criteria that define characteristics that affect the look of the golf course. These methods are then organized into a metric structure with the respective evaluation criteria. Using the two re-designed options of Lakeside Hills Municipal Golf Course in Olathe, Kansas as the site for application, the methodologies are evaluated for three different scenarios, the traditional turf course, a partial replacement with synthetic turf, and a full replacement, and given a score. This score provides a quantitative value to weigh the ecologic, economic, and aesthetic benefits and constraints of synthetic turf in a golf course application, and important initial step in discovering its viability in the golf course design industry.
Keywords: Synthetic Turf; Golf Course; Landscape Architecture (0390)